Music production by voice commands in a sound perception application - Passos, Leonardo Porto; Fornari, José (Revista Hipótese, 2022)
In this article, we present the prototype of a web application accessible to the visually impaired for music production education and training in sound perception. Through voice commands, the user can mix the music being played by adding and removing musical instruments and audio effects and changing panning. Mixing is of fundamental importance in the musical recording process, but many listeners and musicians are unaware of the tools and techniques used in this stage, not being able to identify such procedures, which give uniqueness and special aesthetic characteristics to a recording, which motivated the development of the proposed app.